THE QUALITY OF TRANSLATION RESULTS BY GOOGLE TRANSLATE AND MICROSOFT TRANSLATOR IN TRANSLATING CLASSICAL ARABIC TEXTS BASED ON THE TRANSLATION OF THE BOOK MATN AL-GHĀYAH WAT TAQRIB BY FAIZ EL MUTTAQIN - Aida Zavirah Fayruza; Irhamni Irhamni; Achmad Tohe (Fakultas Sastra Universitas Negeri Malang, 2020)
THE QUALITY OF TRANSLATION RESULTS BY GOOGLE TRANSLATE AND MICROSOFT TRANSLATOR IN TRANSLATING CLASSICAL ARABIC TEXTS BASED ON THE TRANSLATION OF THE BOOK MATN AL-GHĀYAH WAT TAQRIB BY FAIZ EL MUTTAQINAbstract: This study aimed to describe the quality of translations results by Google Translate and Microsoft Translator in translating classical Arabic texts based on the translation of the book Matn Al-Ghāyah wat Taqrib by Faiz El Muttaqin by looking at three aspects in the target language; accuracy, acceptability, and readability. The data of this study were analyzed using comparative qualitative research methods. The results showed that Google Translate got a better score than Microsoft Translator. However, both of them produced inaccurate, unacceptable and illegible translations because machine translation cannot properly communicate the meaning and dynamics of the source language into the target language.Keywords: Machine translation, Translation quality, Google translate, Microsoft translatorKUALITAS HASIL TERJEMAH GOOGLE TRANSLATE DAN MICROSOFT TRANSLATOR DALAM PENERJEMAHAN TEKS KLASIK BAHASA ARAB BERDASARKAN TERJEMAHAN KITAB MATN AL-GHĀYAH WAT TAQRIB KARYA FAIZ EL MUTTAQIN Abstrak: Tujuan penelitian ini adalah mendeskripsikan kualitas hasil terjemahan google translate dan microsoft translator dalam penerjemahan teks klasik bahasa Arab berdasarkan terjemahan kitab Matn Al-Ghāyah wat Taqrib karya Faiz El Muttaqin, dengan melihat tiga aspek dalam bahasa sasaran yaitu keakuratan, keberterimaan, dan keterbacaan. Data penelitian ini dianalisis menggunakan metode penelitian kualitatif komparatif. Hasil penelitian menunjukkan bahwa google translate memperoleh skor yang lebih unggul daripada microsoft translator. Kendati demikian, keduanya sama-sama menghasilkan terjemahan yang tidak akurat, tidak berterima dan tidak terbaca karena mesin penerjemahan tidak bisa mengkomunikasikan makna dan dinamika bahasa sumber ke dalam bahasa sasaran dengan benar.Kata kunci: Mesin penerjemah, Kualitas, terjemahan, Google translate, Microsoft translator الملخص: تهدف هذه الدراسة إلى تحليل جودة نتائج ترجمة مترجم جوجل و مترجم مايكروسوفت في ترجمة النصوص العربية الكلاسيكية بناءً على ترجمة كتاب المتن الغاية والتقريب للفائز المتقين، من خلال النظر إلى ثلاثة جوانب في اللغة المستهدفة وهي الدقة والمقبولية وسهولة القراءة. في هذه الدراسة، تم تحليل البيانات باستخدام الطريقة النوعية المقارنة. أظهرت النتائج أن نتائج مترجم جوجل أفضل من مترجم مايكروسوفت. ومع ذلك ، فقد أنتج كلاهما ترجمة غير دقيقة و غير مقبولة و غير واضحة لأنهما لا يستطيعان توصيل معاني و ديناميات مصادر البيانات بشكل صحيحة إلى اللغة المستهدفة الكلمة المفتاح: آلة الترجمة ، جودة ، ترجمة ، مترجم جوجل ،